Novel bispecific PSMA/GRPr targeting radioligands with optimized pharmacokinetics for improved PET imaging of prostate cancer - Liolios, Christos; Schäfer, Martin; Haberkorn, Uwe; Eder, Matthias; Kopka, Klaus (Bioconjugate chemistry, 2016)
A new series of bispecific radioligands (BRLs) targeting prostate-specific membrane antigen (PSMA) and gastrin releasing peptide receptor (GRPr), both expressed on prostate cancer cells, was developed. Their design was based on the bombesin (BN) analogue, H2N-PEG2-[d-Tyr6,β-Ala11,Thi13,Nle14]BN(6-14), which binds to GRPr with high affinity and specificity, and the peptidomimetic urea-based pseudoirreversible inhibitor of PSMA, Glu-ureido-Lys. The two pharmacophores were coupled through copper(I)-catalyzed azide-alkyne cycloaddition to the bis(tetrafluorophenyl) ester of the chelating agent HBED-CC via amino acid linkers made of positively charged His (H) and negatively charged Glu (E): -(HE)n- (n = 0-3). The BRLs were labeled with 68Ga, and their preliminary pharmacological properties were evaluated in vitro (competitive and time kinetic binding assays) on prostate cancer (PC-3, LNCaP) and rat pancreatic (AR42J) cell lines and in vivo by biodistribution and small animal PET imaging studies in both normal and tumor-bearing mice. The IC50/Ki values determined for all BRLs essentially matched those of the respective monomers. The maximal cellular uptake of the BLRs was observed between 20 and 30 min. The BRLs showed a synergistic ability in vivo by targeting both PSMA (LNCaP) and GRPr (PC-3) positive tumors, whereas the charged -(HE)n- (n = 1-3) linkers significantly reduced the kidney and spleen uptake. The bispecific (PSMA and GRPr) targeting ability and optimized pharmacokinetics of the compounds developed in this study could lead to their future application in clinical practice as more sensitive radiotracers for noninvasive imaging of prostate cancer (PCa) by PET/CT and PET/MRI.
Gesehen am 02.06.2020